CALLOVIAN RADIOLARIANS FROM THE LOWERMOST CALCARE SELCIFERO DI FONZASO AT PONTE SERRA (TRENTO PLATEAU, SOUTHERN ALPS, ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2008)
This paper deals with radiolarian biostratigraphy of the Calcare Selcifero di Fonzaso at the type-section of Ponte Serra (Southern Alps, Italy). The Ponte Serra section is located on the easternmost part of the Trento Plateau and represents an early-drowned sector that marks the transition to the Belluno Trough.The Calcare Selcifero di Fonzaso consists of pelagic siliceous limestones of Middle to Late Jurassic age for a total thickness of about 70 m. A 24 metres thick package of resedimented limestone is interstratified. This research is focused on the lowermost part, 9 metres thick, that mainly consists of red and green siliceous micrites with interbedded clay beds and abundant chert lenses and nodules. The studied interval lies between the lower member of the Rosso Ammonitico Veronese Formation below and the resedimented limestone above. The recovered radiolarian assemblages indicate a Callovian age for the base of the Calcare Selcifero di Fonzaso. Correlation with other sections of the Trento Plateau reveals a significant diachronism in siliceous sedimentation that we relate to highly irregular sea-bottom paleotopography. The base of siliceous deposits can be even older (Bathonian) on the eastern margin of the Trento Plateau, but younger (Oxfordian) on its western margin. The Callovian succession of the Belluno Trough consists of radiolarian-bearing micrite alternating with oolitic limestone. The oolitic sands that filled in the Belluno Trough during the Middle Jurassic prograded over the eastern margin of the Trento Plateau in the early Oxfordian.
Keywords: Siliceous limestone; Radiolarians; Biostratigraphy; Middle Jurassic; Trento Plateau; Belluno Trough; Southern Alps; Italy